Productivity Analysis of Production Units using Objective Matrix and Root Cause Analysis Methods - Nugroho, Ayyasy; Aryanny, Enny (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
PT XYZ is a company engaged in the liquefied petroleum gas (LPG) processing industry. In recent years, the company has faced significant fluctuations in production, deviating from its established targets. This issue has led to a decline in productivity over time. To address this, the study applies the Objective Matrix (OMAX) method to analyze key performance factors measuring LPG productivity from October 2023 to September 2024. The OMAX calculations reveal fluctuations, with the highest achievement recorded in August 2024 at 961.8 and the lowest in February 2024 at 173. Root Cause Analysis (RCA) was conducted to identify the primary causes of productivity decline, uncovering three critical factors: raw materials (Ratio 1), machine operating hours (Ratio 3), and idle machine hours (Ratio 4). These factors significantly contributed to reduced productivity due to unstable feed gas supply, high contamination levels affecting feed gas quality, machine downtime, and insufficient supervision and employee training. To enhance LPG productivity in the future, this study recommends several improvement strategies, including the development of gas exploration and extraction, strengthening raw material quality monitoring systems, implementing a more structured maintenance and repair plan, and providing intensive training programs for workers.